EFEKTIVITAS PENGGUNAAN BAHAN AJAR PASAL 33 1945 - Achmadi Achmadi; M Basri (Jurnal Visi Ilmu Pendidikan, 2021)
AbstractThis article is intended to measure the effectiveness of using Article 33 of the 1945 Constitution for junior high school students and the improvement of teaching materials, in accordance with the principles of development. As an experimental research, the form of this research is a quasy experiment. The object of this research was 53 students in SMP Kota Singkawang. Data were collected using measurement techniques. This study uses a different test using t-test as a data analysis tool. Based on the SPSS output, the t-test results show that the significance = 0.00 <α 0.05, which indicates that there is a significant difference in learning outcomes between the pre-test and post-test results. Thus it can be concluded that the effective use of teaching materials has an impact on students' understanding of the material of Article 33 of the 1945 Constitution at SMP Kota Singkawang. Keywords: Economic Learning, Teaching Materials, Article 33 of the 1945 Constitution.